External Morphological Study of Diplacodes Triviales Rambure(Odonata :Libellulidae)New Record to Iraq - Abd, I. F.; Al-Asady, H. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
External Morphologicalstudy of species DiplacodestrivialesRambure of family : Libellulidae from suborder Anisoptera of the order Odonata which were collected from Maisan Governorate 2010. such study was included : Detailed description of most body parts (Head, Thorax,Abdomen and their appendages), identification and recognition of species, study male and female genitalia. The species Diplacodes Triviales Rambure was new record to Iraqi fauna of Odonata.